Barriers and Facilitators to Substance Use Treatment in the Rural South: A Qualitative Study. Issue 1 (15th July 2015) - Browne, Teri; Priester, Mary Ann; Clone, Stephanie; Iachini, Aidyn; DeHart, Dana; Hock, Robert
Abstract: Purpose: Little qualitative research has examined factors associated with care in substance abuse treatment agencies in Southeastern rural communities. This study explored client‐ and agency stakeholder‐perceived barriers and facilitators to substance use treatment delivery in southeastern rural communities. Methods: Group and individual interviews were conducted with 40 key stakeholders and 40 clients at 9 substance abuse agencies serving rural communities in a southeastern state. Qualitative thematic analysis was used to identify perceived barriers and facilitators to substance abuse services in rural communities. Findings: Four primary themes emerged from the client and stakeholder interviews as both barriers and facilitators: availability of services for individuals with substance use disorders; access to the current technology for client services and agency functioning; cost of services; and stigma. Conclusions: This study identifies novel barriers and facilitators to substance use care in the rural South and highlights essential areas for consideration when developing and implementing substance use care in this geographic region. These findings can be used as guidelines to provide better care to individuals with substance use disorders living in rural communities.